Optimisation of Water Volume Consumption in Commercial Aircraft - Samsudin, Muhmaammad Naqiuddin Bin; Abdul Ghafir, Mohammad Fahmi bin (Progress in Aerospace and Aviation Technology, 2024)
This research paper focuses on optimising water volumes consumed in commercial aircraft water tanks during flying to reduce fuel consumption and promote sustainability. The study employs a methodology that includes real data collection, statistical analysis, and optimisation using the Response Surface Methodology (RSM). The data obtained from Boeing 787-9 and 787-10 fleets used in this study spans from December 2022 to March 2023. The findings and analyses are based on various parameters such as water usage, flight duration, and passenger count. Statistical comparisons between the water usage optimised by RSM and the present estimation model developed by the International Air Transport Association (IATA) and Boeing methods are conducted, highlighting the superior performance of RSM in terms of lower percentage errors and better optimisation. The frequency distributions of percentage errors provide further support for the effectiveness of RSM. This research significantly contributes to our understanding of optimising aircraft water usage for improved fuel efficiency and sustainability. The findings have important implications for the aviation industry and environmental preservation. By reducing fuel consumption through optimised water volumes, airlines can enhance operational efficiency while minimising environmental impact.